Regime Jurídico Mínimo das Comissões Parlamentares de Inquérito - Mateus, Marcos Pedroso (2006)
The aim of this dissertation is to identify and study, in te context of the Brazilian juridical system, the most relevant aspects of the entity called Congressional Investigation Committee in order to understand which are the existing applicable juridical norms as well as the interpretation of these norms provided by the Federal Supreme Court. The first step is to identify the origins and sources of the power of these committees. This is done through the analysis of some of the fundamental principles of the Democratic State of Right instituted by the 1988 Federal Constitution. The following step is to know which are the tools that the Congressional Investigation Committees can use in order to accomplish their mission, and which are the limits of their action, given that there are no unlimited powers under the. The Parliament is the locus of the Congressional Investigation Committees. They constitute a fundamental tool for the exercise of the investigation of the public administration. This investigation function is part of the ordinary competence of oversight which is constitutionally and exclusively conferred to the Legislative Power